Miracle in the rain [videorecording (DVD)] - Rosenberg, Frank P.; Hecht, Ben, 1894-1964; Maté, Rudolph, 1899-1964; Wyman, Jane, 1917-2007; Johnson, Van, 1916-2008; Castle, Peggie, 1927-1973; Clark, Fred, 1914-1968; Heckart, Eileen, 1919-2001; Hutchinson, Josephine, 1903-1998; King, Alan, 1927-2004; Hecht, Ben, 1894-1964 (Distributed by Warner Home Video, 2007)
A secretary accepts an impulsive marriage proposal from an army private just before he is dispatched overseas to fight in World War II. When she receives news of his death, her suffering becomes unbearable-- until a miracle occurs.